The contribution of bacteria and fungi to soil biological activity in a Pinus pinea wood on Vesuvius mount - Papa S.; Pellegrino A.; Fioretto A. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Streptomycin and cycloheximide were applied alone or in combination to the upper soil layer (0-5 cm) of a Pinus pinea forest to determine their effects on CO2 evolution dynamics, enzyme activities, such as dehydrogenase and hydrolase, microbial biomass N, N-mineralization and N-nitrification. The biocide-treated soil had less respiration than the control. Consistently with the pattern of microbial respiration, microbial biomass N as well as N-NH4+ and N-NO3 contents, had a lower level in the treated samples than the control samples. The contribution of fungi to soil respiration was greater than bacteria in every sample in every season. Both dehydrogenase and hydrolase were more active during the winter and spring than in summer and autumn.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)